TINJAUAN YURIDIS PENGATURAN PENINJAUAN KEMBALI BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 34/PUU-XI/2013 DIKAITKAN ASAS LITIS FINIRI OPORTET - Nadya Safitri; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Review is regulated in Article 268 Paragraph 3 of the Criminal Procedure Code(KUHAP) "Limiting an application for review of a decision can only be filed once". Based on thedecision of the Constitutional Court Number 34/PUU-XI/2013 stated that Article 268 Paragraph3 of the Criminal Procedure Code against the 1945 Constitution of the Republic of Indonesiameans that a review cannot only be submitted once but may deny the principle of litis finiriopportet more than once. Therefore, the purpose of this thesis research is first, to find out theregulatory mechanism for judicial review in criminal cases after the Constitutional Court'sdecision Number 34/PUU-XI/2013 is related to the principle of litis finiri opportet. Second,knowing the relationship between legal certainty and justice after the Constitutional Court'sdecision Number 34/PUU-XI/2013 is related to the principle of litis finiri opportet.This type of research can be classified into the type of normative legal research. Thisstudy used secondary data consisting of primary legal materials, secondary legal materials,tertiary legal materials and data collection techniques were carried out using the library studymethod.From the results of the research problem there are two main things that can be concluded.First, the Mechanism for Review Arrangements in criminal cases following the ConstitutionalCourt decision Number 34/PUU-XI/2013 associated with the principle of finiri opportet is notregulated regarding the limitation of review. cases will never be finished which has run awayfrom the principle of litis finiri opportet (A case must have an end). Second, the relationshipbetween the principle of legal certainty and the principle of justice after the decision of theconstitutional court Number 34/PUU-XI/2013 is associated with the principle of litis finiriopportet: This Constitutional Court decision has denied the principle of litis finiri opportet,namely that every case must have an end, the aim of which is to realize justice and findingmaterial truth. The author's suggestion is First, the government follows up regarding the settingfor limiting the number of times you can apply for a PK. Second, it is suggested that judicialpower, both the Supreme Court and the Constitutional Court, is expected to combine 3 (three)important things in deciding cases, namely legal certainty, expediency, and justice.Keywords: Judicial Review - Constitutional Court - Litis Finiri Oportet Principle.